KONTRIBUSI ALTRUISME DAN IKLIM ORGANISASI TERHADAP KINERJA GURU SMA SE-KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - SOFYA SARI; ISJONI ISJONI; DAENG AYUB NATUNA (Jurnal JUMPED (Jurnal Manajemen Pendidikan), 2017)
The aim of this research to determine the contribution of variable (1) altruismwith the performance of teacher (2) organizational climate on teacher performance (3) altruismand organizational climate on teacher performance. The Respondents were senior high schoolteachers at Tanah Putih sub-district RokanHilir district which amounts to 101 gained bysimplerandom sampling Proportional techniques. The accumulation of data is conducted througha questionnaire as a research instrument. The analysis of data is using descriptive analysis,inferential statistical analysis and hypothesis. Instrument reliability coefficient is calculated byusing Cronbach alpha. The result of research shows the contribution between the altruism ofteacher performance by 0,667, and there is a contributions Organizational Climate on teacherperformance by 0,243. Whereas simultaneously, contributions altruism and organizational climateon teacher performance by 0.707